Indian palaemonid decapod crustaceans : taxonomic status, research challenges and conservation needs - JAYACHANDRAN, K V (The Indian Journal of Animal Sciences, 2010)
Prawns and shrimps comprise about 2500 species and are distributed throughout the world. They belong to complex taxonomic groups. The prawns of the family Palaemonidae Rafinesque, 1815 are highly important on both commercial as well as ecological point of view. Extensive studies on the biodiversity and taxonomy of Indian freshwater prawns have been carried out by many and they have recorded 75 species belonging to 8 genera under the subfamily Palaemoninae Rafinesque, 1815 and these prawns inhabit a wide range of habitats from hill top to estuaries. The present paper provides a comprehensive account on various aspects such as diversity of species, state wise distribution of species, taxonomic status and confusion, molecular taxonomy, karyological information, distribution based on their habitat, present level of utilization of diversity, research challenges and also ex situ and in situ conservation methods and needs of palaemonid prawns of India.